Complexities and Uncertainties in Transitioning Small-Scale Coral Reef Fisheries - Leenhardt, Pierre; Lauer, Matthew; Madi Moussa, Rakamaly; Holbrook, Sally J.; Rassweiler, Andrew; Schmitt, Russell J.; Claudet, Joachim (Frontiers in Marine Science, 2016)
Coral reef fisheries support the development of local and national economies and are the basis of important cultural practices and worldviews. Transitioning economies, human development and environmental stress can harm this livelihood. Here we focus on a transitioning social-ecological system as case study (Moorea, French Polynesia). We review fishing practices and three decades of effort and landing estimates with the broader goal of informing management. Fishery activities in Moorea are quite challenging to quantify because of the diversity of gears used, the lack of centralized access points or markets, the high participation rates of the population in the fishery, and the overlapping cultural and economic motivations to catch fish. Compounding this challenging diversity, we lack a basic understanding of the complex interplay between the cultural, subsistence, and commercial use of Moorea's reefs. In Moorea, we found an order of magnitude gap between estimates of fishery yield produced by catch monitoring methods (~2 t km-2 year-1) and estimates produced using consumption or participatory socioeconomic consumer surveys (~24 t km-2 year-1). Several lines of evidence suggest reef resources may be overexploited and stakeholders have a diversity of opinions as to whether trends in the stocks are a cause for concern. The reefs, however, remain ecologically resilient. The relative health of the reef is striking given the socio-economic context. Moorea has a relatively high population density, a modern economic system linked into global flows of trade and travel, and the fishery has little remaining traditional or customary management. Other islands in the Pacific that continue to develop economically may have small-scale fisheries that increasingly resemble Moorea. Therefore, understanding Moorea's reef fisheries may provide insight into their future.